Sosialisasi Manajemen Penyelenggaraan PAUD - Mahkamah Brantasari (Sekolah Tinggi Teknologi Industri (STTI) Bontang, 2021)
Paud is an organization engaged in early childhood education that must be very well managed and maximally organized because paud is a learning platform that focuses on children who have a golden age whose time span is only short and must be really serious in implementing the learning system so that it is in line with the goals and directions of early childhood education. Planning is the initial foundation of an activity can and will be carried out, in planning made a goal, which is summarized in the vision and mission of the organization, the next activity is organizing, after planning then what must be considered is how activities can be carried out properly according to objectives, activities that must be carried out is the distribution of tasks to experts in accordance with predetermined fields. Furthermore, the implementation of the plans that have been made, implementation is a process that is carried out continuously repeatedly so that there is a need for a control or supervision to ensure that the implementation of activities runs well in accordance with the provisions that have been planned.